2019
DOI: 10.1029/2017jg004315
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Microbial Community Patterns During Incipient Soil Formation From Basalt

Abstract: Microbial dynamics drive the biotic machinery of early soil evolution. However, integrated knowledge of microbial community establishment, functional associations, and community assembly processes in incipient soil is lacking. This study presents a novel approach of combining microbial phylogenetic profiling, functional predictions, and community assembly processes to analyze drivers of microbial community establishment in an emerging soil system. Rigorous submeter sampling of a basalt-soil lysimeter after 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 115 publications
(142 reference statements)
2
21
0
Order By: Relevance
“…Stegen et al (2012) originally demonstrated that stochastic processes contribute proportionally more to community assembly when environmental stresses were low. Recent work of Tripathi et al (2018) and Sengupta et al (2019) has supported this assumption: stochasticity was dominant under mild environmental conditions, whereas determinism contributed a greater proportion of assembly processes under extreme conditions. Flooding can also promote soil fertility in rice paddies and lead to higher resource bioavailability that releases micro‐organisms from environmental stresses (Chen, Zhang, & Effland, 2011; Feng, Chen, et al, 2018; Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Stegen et al (2012) originally demonstrated that stochastic processes contribute proportionally more to community assembly when environmental stresses were low. Recent work of Tripathi et al (2018) and Sengupta et al (2019) has supported this assumption: stochasticity was dominant under mild environmental conditions, whereas determinism contributed a greater proportion of assembly processes under extreme conditions. Flooding can also promote soil fertility in rice paddies and lead to higher resource bioavailability that releases micro‐organisms from environmental stresses (Chen, Zhang, & Effland, 2011; Feng, Chen, et al, 2018; Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Previous investigations found a predominate role for determinism in upland agroecosystems that was associated with intensive anthropogenic activities, such as wildfires, repeated fertilization, plowing and tillage (Knelman, Schmidt, Garayburu‐Caruso, Kumar, & Graham, 2019; Prach & Walker, 2011). These repeated external disturbances are thought to select for specific species capable of tolerating such perturbations (Fan et al, 2017; Feng, Adams, et al, 2018; Feng et al, 2017; Ferrenberg et al, 2013; Sengupta et al, 2019). In contrast to upland ecosystems, we found that turnover of microbial communities in paddy agroecosystems was primarily dominated by stochasticity (Figure 3; Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The systematic shifts in chemical characteristics of soil-carbon fractions exhibited by samples at the shallow depth suggest that organic C compound pools in shallower soil depths are sensitive to salinity gradients, while deeper depth signatures do not vary systematically across the landscape. The landscape gradient observed in the shallow soils is likely influenced by a combination of reduced litterfall due to trees suffering under recent increases in salinity, changing understory vegetation, and algae-rich particulate OM deposition during inundation events that presumably initiated after the recent culvert removal (Wang et al, 2019). In contrast, the deeper soil depths were more simi- lar to older organo-mineral complexed C in terrestrial soils across various ecosystems and land uses (Conant et al, 2011;Dungait et al, 2012;Jobbágy and Jackson, 2000;Gleixner, 2006, 2008).…”
Section: Molecular Characterization Reveals Chemical Gradients Not Sementioning
confidence: 99%
“…The incipient soil is basaltic crushed tephra sourced from Merriam crater in northern Arizona and is being extensively studied at the Landscape Evolution Observatory (LEO) housed at Biosphere 2 in University of Arizona, to understand coupled hydrobiogeochemical processes of landscape evolution [17,18]. This lithogenic basalt parent material is oligotrophic, with low carbon content (0.001 ug/mg) [19] but has been shown to harbor microbial life [20]. The objectives of this study were to (i) evaluate germination capacity and plant growth capacity of the basaltic parent material, (ii) compare plant growth in parent material with and without compost amendment as compared to potting soil, and (iii) assess soil microbial community composition and functional potential between treatments.…”
Section: Land Degradation Neutrality (Ldn) Program Adopted By the Unimentioning
confidence: 99%
“…Soil microbial DNA from the frozen soils was extracted and sent for sequencing to the University of Arizona Genetics Core (UAGC; Tucson, AZ, USA). Sequence data was analyzed as per protocols highlighted in Sengupta et al 2018 [20]. Briefly, paired-end sequencing (2x150 bp) was performed on the bacterial and archaeal 16S rRNA gene V4 (515F-806R primers) hypervariable region using the Illumina MiSeq platform (Illumina, CA, USA) [33].…”
Section: Soil Microbial Community Analysismentioning
confidence: 99%